2021
DOI: 10.1590/s1678-9946202163057
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis and budgetary impact of the Cryptococcal Antigen Lateral Flow Assay (CRAG-LFA) implementation for the screening and diagnosis of cryptococcosis in asymptomatic people living with HIV in Brazil

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…The presence of Cryptococcosis in the central nervous system leads to severe neurological complications [2,3,7,10]. In recent years, great advances have been described in development of laboratory techniques for the diagnosis of infectious diseases and in the emergence of new methodologies for the diagnosis of Cryptococcus spp., especially in HIV-positive individuals [21][22][23][24][25][26]28,[32][33][34][35][36]40,41]. However, the problem of early accurate diagnosis still remains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of Cryptococcosis in the central nervous system leads to severe neurological complications [2,3,7,10]. In recent years, great advances have been described in development of laboratory techniques for the diagnosis of infectious diseases and in the emergence of new methodologies for the diagnosis of Cryptococcus spp., especially in HIV-positive individuals [21][22][23][24][25][26]28,[32][33][34][35][36]40,41]. However, the problem of early accurate diagnosis still remains.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the laboratory diagnosis of Cryptococcus spp. is based on mycological, histopathological and serological tests [17][18][19][20][21][22][23][24][25][26]. The Brazilian Unified Health System (SUS) provides different methods for the diagnosis of CM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with CD4 < 100 cells/µL, studies employing the CRAG-latex test have already demonstrated a 20-40% reduction in disease-associated mortality [51,52], preventing 43% of CM deaths even at a low prevalence of 1.4% [17]. In Brazil, a cost-effectiveness study based on the prevalence of 3.09% in HIV-infected patients with CD4 < 200 cells/µL showed that two cryptococcal antigen tests (CRAG-latex and LFA) are cost-effective in patients with CD4 < 200 cells/µL compared to India ink and no screening, with LFA proving superior to CRAG-latex, avoiding 15% of deaths by CM and decreasing costs by 11 million US dollars in five years [33]. Recently, the cryptococcal antigen lateral flow assay diagnostic test for the detection of Cryptococcus infection in PLHA was incorporated for use in the Unified Health System (SUS) by the Ministry of Health, for patients with CD4 < 200 cells/µL and for the diagnosis of CM in PLHA regardless of CD4+ cell count [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is largely cost-effective compared to inpatient treatment of CM, considering both the CRAG-latex [16,32] and LFA [17,19] diagnostic tests. In addition to the benefit of being a point-of-care test, in Brazil, the cost-benefit of LFA is even higher than the CRAG-latex in people living with HIV/AIDS (PLHA) with CD4 ≤ 200 cells/µL [33].…”
Section: Introductionmentioning
confidence: 99%